Constructive Strategy of Amine Functionalization on Cu−In−Zn−S With N→Cu Coordination for Efficacious Photocatalytic Hydrogen Evolution - Mengmeng Ma; Runkang Lin; Kaige Huang; Shizhong Yue; Maohong Fan; Zhijie Wang; Shengchun Qu (Carbon Energy, 2025)
ABSTRACT Functionalization has emerged as a pivotal endeavor to tailor the surface properties of photocatalysts. We propose a facile amine functionalization strategy to establish a Cu−In−Zn−S (CIZS)/NiSx hybrid with covalent bonds using individual ethylenediamine (EDA) molecules. Our approach witnesses a remarkable photocatalytic hydrogen evolution (PHE) competence of 65.93 mmol g−1 h−1 driven by visible light, the highest value yielded by CIZS to date. X‐ray absorption spectra of CIZS and density functional theory (DFT) calculations confirm the crucial amine N→Cu coordination after amine functionalization. The new emerging coordination via lone‐pair electron donation profitably accesses the regulation of the coordination environment, electronic structures, and carrier behavior. Moreover, individual EDA molecule with two‐terminal −NH2 group serves as a molecular bridge to hybrid CIZS and NiSx cocatalyst via N→Cu and N→Ni coordination, favorably promoting efficient charge transport. This study provides advances in practical functionalizing photocatalysts.